Spatial analysis of secondary vocational education in Anbar province and ways to develop it - AlQaisi, Istabraq (Al-Adab Journal, 2023)
Secondary vocational education is an important necessity for the human development process, and the provision of skilled average human cadres to meet the needs of the local market, after absenteeism and neglect that afflicted this type of education on the one hand, and low enrollment rates on the other hand. The researcher chose the topic tagged "spatial analysis of secondary vocational education in Anbar Governorate and ways to develop it" to reveal the philosophy of vocational education in Anbar Governorate, and to identify the most prominent problems and challenges facing the vocational education sector, so it was necessary to develop a geographical vision that discusses the most important ways to enable and develop the reality of education professional in the province. The results of the research showed the absenteeism and neglect that afflicted this important educational sector and the non-optimal signature of vocational education schools, as the districts of (Al-Habbaniyah, Al-Karma, Al-Rutba) lack the presence of vocational schools in them, in addition to the curricula being outdated and relatively lagging behind the actual need, which affected the low enrollment rates. Therefore, it is imperative for us to create a promising and supportive learning environment for the sustainable development process.